Предмет: Алгебра,
автор: juli1860
упростить выражение
3а -7b - 6a + 8b
3(4x+2)-6
10x-(3x+1)+(x-4)
20 (2y-1)-3 (y+2)
Ответы
Автор ответа:
0
b-3a
12x+6-6=12x
10x-3x-1+x-4=8x-5
40y-20-3y-6=37y-26
12x+6-6=12x
10x-3x-1+x-4=8x-5
40y-20-3y-6=37y-26
Автор ответа:
0
Спасибо
Автор ответа:
0
-3а+b
12x
8x-5
37y-26
Я надеюсь, что помогла
12x
8x-5
37y-26
Я надеюсь, что помогла
Автор ответа:
0
Спасибо
Похожие вопросы
Предмет: Физика,
автор: silencio0804
Предмет: Математика,
автор: coe3719
Предмет: Алгебра,
автор: asanali200151
Предмет: Литература,
автор: Аноним
Предмет: Геометрия,
автор: hellostranger